Arthroscopic Treatment for Primary Septic Arthritis of the Hip in Adults. (5th October 2016) - Schröder, Jörg Hartmut; Krüger, David; Perka, Carsten; Hufeland, Martin
Abstract : Purpose. Primary septic arthritis is a rare differential diagnosis of acute hip pain in adults. Inspired by the success of all-arthroscopic treatment in pediatric patients, we developed a diagnostic and surgical pathway for our adult patients. Methods. Seven patients, average age 44 ± 13.7 years with acute hip pain since 4.4 ± 2.9 days in the average, were included. Septic arthritis was confirmed by joint aspiration and dissemination was excluded by MRI and standard radiographs. Surgical treatment consisted of immediate arthroscopic lavage using 4 portals for debridement, high-volume irrigation, partial synovectomy, and drainage. Results. Patients were treated in hospital for 12.4 ± 3.1 days (range 7–16 days). WBC and CRP returned to physiological levels. During the mean follow-up of 26.4 ± 19.4 months (range 13–66 months) no patient showed recurrence of infection. The 5 patients with an unimpaired hip joint prior to the infection had a mean modified Harris Hip Score of 94 ± 5.6 points (range 91–100) at final follow-up. Conclusions. Arthroscopic therapy using a minimally invasive approach with low perioperative morbidity for the treatment of primary septic arthritis of the adult hip is able to restore normal hip function in acute cases without dissemination of the infection. Level of Evidence. IV.